Identifying the Benefits of Simulation Videos on the Knowledge and Skills of Anthropometric Measurements of Posyandu Cadres as An Effort to Prevent Stunting - Olivia Bawaeda; Margareeth Bangkut; Dahlia Sinedu (Indonesian Journal of Global Health Research, 2024)
Stunting has a negative impact on children's quality of life, such as impaired brain and cognitive development, failure to thrive, and low immune system. One of the efforts to primary prevent stunting is to provide education to increase the knowledge and skills of posyandu cadres in carrying out anthropometric measurements. Objective This research identifies the educational benefits of video simulations on cadres' knowledge and skills in anthropometric measurements of toddler posyandu cadres. Method the method used in this research is a pre-experimental study, with a one-group pre-post test design approach. The sample was recruited using purposive sampling technique. Result the results of research based on the Wilcoxon analysis test explain that video simulation education is effective in increasing the knowledge and skills of toddler posyandu cadres in anthropometric measurements with a p value of 0.000 (ɑ <0.05). Data was taken using a knowledge questionnaire and skills observation sheet for 25 respondents through a pre-post test. Data distribution based on univariate analysis illustrates that there was an increase in the knowledge and skills of respondents who received the educational intervention of video simulations of anthropometric measurements for toddlers. Conclusion Simulation video education is useful in increasing the knowledge and skills of posyandu cadres in anthropometric measurements. The results of this research can be recommended for application in improving basic knowledge and skills in anthropometric measurements of posyandu cadres and health workers in primary health care facilities and pediatric nursing practice in hospitals.